Development of Flipbook-Based Learning Media on Entrepreneurial Materials for Class XI SMK Tunas Pembangunan - Lutfiah Islamiah; Henry Eryanto; Maulana Amirul Adha (Jurnal Indonesia Sosial Teknologi, 2024)
The purpose of this research is to develop interactive learning media based on flipbooks in office facilities and infrastructure subjects and to determine the feasibility of flipbook-based learning media in the subject of creative products and entrepreneurship class XI at SMK Tunas Pempembangunan. The type of research used is research and development (RnD) using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development method. Data collection was conducted using interviews with teachers of SMK Tunas Pempembangunan. The feasibility of learning media is assessed by media experts and material experts. Data analysis was carried out by qualitative and quantitative analysis. Based on research that has been carried out on flipbook-based interactive learning media that has been developed as a result of expert validation, it is known that interactive learning media using heyzine flipbook in the subject of creative products and entrepreneurship class XI is very feasible to use. The average result of media experts is 85.36%. And material experts 92.19%, so it is categorized as "very feasible" as an interactive learning medium.